Characterization of exosomal RNAs derived from human gastric cancer cells by deep sequencing - Jia Ren; Quan Zhou; Hao Li; Jianfang Li; Li Pang; Liping Su; Qinlong Gu; Zhenggang Zhu; Bingya Liu (Tumor Biology, 2017)
Exosomes secreted from the cell to the extracellular environment play an important role in intercellular communication. Next-generation sequencing technology, which has achieved great development recently, allows us to detect more complete data and gain even deeper analyses of RNA transcriptomes. In our research, we extracted exosomes from different gastric cancer cell lines and immortalized normal gastric mucosal epithelial cell line and examined the amounts of exosomal proteins and RNAs. Our data showed that the secreted amount of cancer cell–derived exosomes, which contain proteins and RNAs, was much higher than that of normal cell–derived exosomes. Moreover, next-generation sequencing technology confirmed the presence of small non-coding RNAs in exosomes. Based on publicly available databases, we classified small non-coding RNAs. According to the microRNA profiles of exosomes, hsa-miR-21-5p and hsa-miR-30a-5p were two of the most abundant sequences among all libraries. The expression levels of the two microRNAs, miR-100 and miR-148a, in exosomes were validated through reverse transcription polymerase chain reaction. The reverse transcription polymerase chain reaction result, consistent with the trend of sequencing result, indicated a significant difference in exosomes between gastric cancer and gastric mucosal epithelial cell lines. We also predicted novel microRNA candidates but they need to be validated. This research provided an atlas of small non-coding RNA in exosomes and may make a little contribution to the understanding of exosomal RNA composition and finding parts of differential expression of RNAs in exosomes.